Re-socializing emptied spaces: a queer-feminist performance, the theatrical apparatus and its (post)pandemic epistemology. Issue 1 (2nd January 2023) - Otto, Ulf
ABSTRACT: The suspension of operations during lockdowns facilitated a new perspective on performance: the absent came to appear as a determining factor of not only the pandemic, but became evident as constitutive of late modern theater cultures. Based on a description of the lockdown performance A Room of Our Own (2021) by the feminist collective Swoosh Lieu, it is shown how contemporary practice is relocating performance within its entanglement with the social spaces of reproduction. Emphasizing the realities of exclusion that the performing arts rest upon, the paper argues against a theory of performance as an enclosed event of participation based on an idealized idea of the social as a homogeneous microcosm. It calls instead for an empirics of assembly, and more generally to question a thinking of performance along the lines of interaction and communication. Adopting Karen Barad's concept of posthuman performativity to Theater Studies, it foregrounds the mediating function of performance in its articulation of the world and proposes to reconceptualize theater as an epistemological apparatus to invigorate a strong program of theater studies that refocuses on the socio-political real of theatricality.